PERANAN EKONOMI SYARÎ’AH DI TENGAH KRISIS GLOBAL - Sakinah - (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2009)
At the end of 2008, the super power United States suffered fromeconomic crisis. It shocked the world since US economic policylegalizes capitalism. Not only US experienced the crisis but alsoother countries did, including Indonesia. The crisis repeatedlyoccurs many times however it is unstoppable. Only those thatapply Islamic economic system endures the crisis. They areArabian countries. The questions had been purposed is that howcome the capitalism easily injured crisis? The hypotheticalanswer is that because economic capitalism allows the practiceof maghrib, the acronym of maysir, gharar, and riba’. These havebeen insulted in Syariah economical system. Ironically, thesethree concepts of capitalism have been applied and adopted byconventional banking such as stock exchange, insurances andmoney market. These are suspiciously caused the downfall ofconventional financing system. This brief article is about todescribe the prohibition of riba (bribery) practice.